First trimester ultrasound detection of fetal micrognathia - Galvão,Ana (2015)
Fetal micrognathia is a rare ocurrence in which there is a small mandible and a receding chin. It can be seen in the sagital view of the face during an obstetric ultrasound and it may be associated with adverse environmental factors, multiple genetic syndromes and with chromosomal abnormalities. The overall prognosis seems to be poor. We present a case of isolated fetal micrognathia, which has been suspected in the first trimester ultrasound and ended in termination of pregnancy.